PEREMPUAN DALAM PERSPEKTIF HUKUM ISLAM - Fauziah, Syarifah (An - Nisa`, 2012)
This paper examines perspectives on woman in Islamic law by displaying two main issues, namely: How does Â the ideology of woman in Islam? And how do Islamic law regarding woman?The ideology of woman is built on the notion that men and woman are in a parallel position. Therefore, the culture and tradition of patriarchal Arab nation has been changed by Islamic revolutionary. Islam always tries to overhaul a culture that marginalizes the position of woman by ordering yhe men to apply good, fair and wise deeds to woman. Therefore, through the Islamic teaching woman are given a proporsional role.Woman in the perspective of Islamic law covers a wide range of legal thought on aspect relating to adult woman in carrying out their activities reflected by detailed arguments. Hence, the woman jurisprudence is essentially the result of understanding or ijtihad of scholars rooted in Qurâan And hadith that governs the presence of woman, both in domestic and in public areas.